Dificuldades e Estratégias na Formação Inicial de pedagogos para o Ensino de Matemática nos Anos Iniciais do Ensino Fundamental: Uma Revisão Sistemática da Literatur - Angeli, Luciane Schllemer (2025)
This thesis, linked to the “Mathematics Education” line of research and to the research group “Grupo de Pesquisa Interfaces em Educação Matemática (GPIEM)”, it discusses the importance of the Initial Training of educators for the Mathematics teaching on the Initial Years of Elementary School. In view of this, the objective of this research is identifying and understanding the difficulties encountered in the initial training of pedagogues for the Mathematics teaching on the Initial Years of Elementary School, as well as the strategies indicated to overcome the difficulties in developed researches. To that end, a Systematic Literature Review (SLR) was carried out with the following guiding question: “What are the difficulties and strategies encountered and/or indicated in/for the Initial Training of pedagogues for the Mathematics teaching on the Initial Years of Elementary School in Brazil, according to developed researches?”. The analysis methodology adopted was the qualitative approach, through the interpretative analysis of data present in documents and published researches. Through data analysis, there are several difficulties on the Initial Training of pedagogues for the Mathematics teaching on the Initial Years of Elementary School. Among the encountered difficulties, the conceptual order ones, related to the understanding of the mathematical contents, and methodological ones, which refer to the knowledge and effective application of appropriate pedagogical practices, stand out. Furthermore, matters related to the conceptions and belief of teachers in training about the Mathematics teaching and the role of Formators are also seen as challenges because the trainers' approach often does not promote an effective articulation between theory and practice, contributing to the fragmented training of future pedagogues. In view of these difficulties, the literature proposes strategies that can be applied on the Initial Training - Methodological alternatives - just as the usage of concrete resources and technological teaching resources, as well as methodologies that encourage a more interactive and contextualized practice. Furthermore, the implementation of Continuous Training programs is suggested as necessary to overcome the gaps identified on the Initial Training and expand the knowledge, as well as promoting professional development.